Characterization of SCCmectype IV methicillin‐resistantStaphylococcus aureusclones increased in Japanese hospitals. Issue 6 (June 2018) - Nakaminami, Hidemasa; Takadama, Shunsuke; Ito, Ayumu; Hasegawa, Mariko; Jono, Chika; Noguchi, Miyuki; Shoshi, Manami; Wajima, Takeaki; Fujii, Takeshi; Maruyama, Hiroshi; Sakamoto, Haruo; Ito, Yutaka; et al.
Abstract : N/A: Recently, the prevalence of staphylococcal cassette chromosome mec (SCC mec ) type IV isolates, which are the major community‐acquired methicillin‐resistant Staphylococcus aureus (MRSA), have increased in Japanese hospitals. The aim of this study was to elucidate the detailed molecular epidemiological features of the SCC mec type IV clones in Japanese hospitals. When 2589 MRSA isolated from four hospitals in Tokyo, Japan between 2010 and 2014 were analysed, the proportion of SCC mec type IV overtook that of type II, which was the major type of hospital‐acquired MRSA in 2014. Multilocus sequence typing showed that CC1 was the most predominant clone in the SCC mec type IV isolates. The clinical departments that the patients belonged to, pulsed‐field gel electrophoresis analysis and antimicrobial susceptibility profiles suggested that the origin of the CC1‐SCC mec type IV (CC1‐IV) clone was a community setting. Our data show that the CC1‐IV clone is becoming a predominant MRSA clone in Japanese hospitals.